Platform Edge Detection and Protection Effects on Platform–Train Interface Safety. Issue 1 (January 2015) - Anderson, Dylan; Hunter-Zaworski, Katharine
The purpose of this study was to provide background information and examples of best practices relating to platform–train interface safety. This paper was adapted from a literature review that was undertaken as part of TCRP Project A-40, which aimed to improve platform safety for rail modes of public transportation. The findings were from an extensive literature review, transit operator safety data, input from two workshops, and interviews with various stakeholders. Information was gathered from transit operators, station designers, station builders, car builders, and accessibility equipment manufacturers. The background research showed that platform safety was primarily affected by technical factors, operational aspects, and passenger characteristics. This study identified possible issues and best practices for the technical design aspects of platform edge safety. Certain factors were found to be universal between modes and could be grouped together. However, the research suggests that each mode has many factors that should be considered separately when potential mitigation strategies are determined. The second part of this paper considers each mode separately.